PROBLEMS OF HEALTH-PRESERVING EDUCATION IN MODERN SCHOOLS (EDUCATION IN THE 21ST CENTURY, 2023)
It is known that excessive learning (mental) load at school age leads to overwork and impairschildren’s health, as there is an imbalance between the interests of education and the health of theyoung generation.The system of continuous education contains all the necessary prerequisites for the formationof a responsible, value-based attitude towards their health. Unfortunately, facts show negativedynamics: there are many more children with health issues among high school students thanamong first-graders. Thus, in the Republic of Armenia, in the first grade only 30 percent ofchildren had health problems, whereas in the sixth grade - 70 percent.The article analyzes the results of the state of health-preserving education in modern schools,draws appropriate conclusions and offers a number of recommendations. The results of the studiesindicate that not only the majority of the interviewed teachers, but also the medical workers ofschools have no idea about health-preserving education.Let's highlight the main reasons:- medical workers in schools are mainly general nurses and are incompetent in organizinghealth-promoting and health-forming education;- teachers solve their problems: to achieve a high-level subject proficiency, to ensure a highlevelacademic performance, etc., whereas the health of students is out of their concern;- there is no enough literature in the Armenian language on the subject, there is no specialseminars and, unfortunately, there is insufficient attention of the heads of educational institutionstowards this important, not to say the most important, issue;- there is weak control, both internal and external.We consider it necessary:- to train medical workers for schools according to a special program;- retrain current workers;- to include courses in valeology (general valeology, pedagogical valeology), the basics ofschool hygiene, etc. in the program of training and retraining of teachers,- to regulate the studyload of schoolchildren.
Keywords: valeology, health, value, workload, student, teacher, textbook, presentation.